The Relationship Between the Striatal Dopaminergic Neuronal and Cognitive Function With Aging - Li, Hongliang; Hirano, Shigeki; Furukawa, Shogo; Nakano, Yoshikazu; Kojima, Kazuho; Ishikawa, Ai; Tai, Hong; Horikoshi, Takuro; Iimori, Takashi; Uno, Takashi; Matsuda, Hiroshi; Kuwabara, Satoshi (Frontiers in Aging Neuroscience, 2020)
Both cognitive function and striatal dopamine function decline by normal aging. However, the relationship among these three factors remains unclear. The aim of this study was to elucidate the association between age-related changes in the striatal dopamine transporter (DAT) and cognitive function in healthy subjects. The 30 healthy volunteers were enrolled in this research, the age ranged from 41.7 to 82.2 (64.5 ± 11.5, mean ± SD). All subjects were scanned with both T1-weighted MRI and 123I-FP-CIT SPECT images. The Wechsler Adult Intelligence Scale-Third Edition (WAIS-III) was used to evaluate cognitive function. Six spherical regions of interest (ROI) using 10mm in diameter on the caudate nucleus (CN), anterior putamen (AP) and posterior putamen (PP) were manually drawn on MRI image which was applied onto SPECT image. The relationship between striatal occipital ratio (SOR) values and WAIS-III subscore were analyzed by multiple regression analysis. Subscores which was significant were further analyzed by path analyses. Full intelligence quotient (IQ), verbal IQ, verbal comprehension were all positively correlated with age-adjusted striatal DAT binding (P < 0.01). Multiple regression analyses revealed that coding digit symbol correlated with all striatal regions except for the left caudate (P<0.04). Picture completion and right caudate, similarities and left caudate also showed positive correlation (P < 0.04). Path analysis found that the right caudate and picture completion; the left caudate and similarities were correlated independently from age, whereas the models of coding digit symbol were not significant. These results suggest that age-based individual diversity of striatal DAT binding was associated with verbal function, and the caudate nucleus plays an important role in this association.